The Legitimacy of Video Call Marriages: Perspectives from Bahtsul Masa'il Nahdlatul Ulama and Majelis Tarjih Muhammadiyah Lampung - Edi, Relit Nur; AS, Susiadi; Muslim (Universitas Islam Negeri Raden Intan Lampung, 2025)
The current development of digital technology has had a significant impact on various aspects of life, including the conduct of marriages. One phenomenon that has emerged is the marriage contract via video call, which allows couples separated by distance to conduct their marriage without having to meet face-to-face. However, this convenience has led to differing opinions regarding the validity of such marriage contracts. Therefore, this study aims to analyze the legitimacy of marriage ceremonies conducted via video call from the perspectives of Bahtsul Masa’il Nahdlatul Ulama (NU) and Majelis Tarjih Muhammadiyah Lampung. This study employs a qualitative approach using a descriptive analytical comparative method. Data was collected through interviews as primary data and document analysis as secondary data. Data processing was conducted through the stages of data reduction, data presentation, and inductive conclusion drawing. The findings indicate that the Bahtsul Masa’il NU Lampung committee considers marriage contracts conducted via video call to be invalid, as they are deemed not to meet the primary requirement of the physical presence of the parties involved. Conversely, the Majelis Tarjih Muhammadiyah Lampung committee provides a more flexible assessment, stating that marriage contracts conducted via video call can be valid if they meet the applicable requirements and conditions of marriage. These findings reflect the dynamics in the interpretation of Islamic law, which can adapt to technological developments while maintaining the fundamental principles of marriage contracts.